2020
DOI: 10.5603/pjnns.a2020.0098
|View full text |Cite
|
Sign up to set email alerts
|

Changes in cervical range of motion following anterior cervical discectomy with fusion — preliminary results

Abstract: Background. The biomechanics of the cervical spine after anterior cervical discectomy with fusion (ACDF), and in particular changes in its global mobility, are phenomena that have not yet been sufficiently studied. Consequently, their effect on the eventual result of treatment is not fully understood. The aim of this study was to assess changes in global and segmental mobility of the cervical spine after ACDF. Material and methods. 28 patients who underwent ACDF for cervical spondylosis were examined. The stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…Our findings regarding the correlation between fusion length and reclination are in line with a previous study by Limanówka and Sagan, on a small number of patients who underwent ACIF in degenerative diseases that reported a correlation between fusion length and range of motion in the sagittal plane [21]. A general reduction in reclination and rotational ability compared to healthy adults after single-level anterior fusion in patients with degenerative disc disease was also reported by Ylinen et al and could also be supported by our findings [22].…”
Section: Resultssupporting
confidence: 92%
“…Our findings regarding the correlation between fusion length and reclination are in line with a previous study by Limanówka and Sagan, on a small number of patients who underwent ACIF in degenerative diseases that reported a correlation between fusion length and range of motion in the sagittal plane [21]. A general reduction in reclination and rotational ability compared to healthy adults after single-level anterior fusion in patients with degenerative disc disease was also reported by Ylinen et al and could also be supported by our findings [22].…”
Section: Resultssupporting
confidence: 92%
“…The mobility retained in adjacent superior and inferior segments can influence abnormal biomechanical loading patterns and ultimately the development of ASD. Limanówka et al ( Limanowka and Sagan, 2020 ) show that in a study of 28 patients who underwent ACDF for cervical spondylosis, patients who developed ASD superior to the fixation site had significantly greater extension range of motion (ROM) compared to those who did not develop ASD (p = 0.032). Such findings are corroborated by Park et al (2007) in a cadaveric model of five cervical spine specimens.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, we have physiotherapists, neurologists and anaesthetists involved in treatment at pain clinics who conduct non-surgical treatments such as physical therapy, immobilisation with orthotics, medications, and spinal injections. On the other hand, there are orthopaedic surgeons and neurosurgeons performing spinal decompression surgery with anterior or posterior stabilisation anteriorly or posteriorly [28,29]. Some studies have suggested that surgical treatment may be more advantageous than non-operative treatment [30,31].…”
Section: Discussionmentioning
confidence: 99%